A New and Compact Wide-Band Microstrip Filter-Antenna Design for 2.4 GHz ISM Band and 4G Applications - Al-Yasir, Yasir I. A.; Alkhafaji, Mohammed K.; A. Alhamadani, Hana’a; Ojaroudi Parchin, Naser; Elfergani, Issa; Saleh, Ameer L.; Rodriguez, Jonathan; Abd-Alhameed, Raed A. (Electronics (Basel), 2020)
A new and compact four-pole wide-band planar filter-antenna design is proposed in this article. The effect of the dielectric material type on the characteristics of the design is also investigated and presented. The filter-antenna structure is formed by a fourth-order planar band-pass filter (BPF) cascaded with a monopole microstrip antenna. The designed filter-antenna operates at a centre frequency of 2.4 GHz and has a relatively wide-band impedance bandwidth of about 1.22 GHz and a fractional bandwidth (FBW) of about 50%. The effects of three different types of substrate material, which are Rogers RT5880, Rogers RO3003, and FR-4, are investigated and presented using the same configuration. The filter-antenna design is simulated and optimised using computer simulation technology (CST) software and is fabricated and measured using a Rogers RT5880 substrate with a height (h) of 0.81 mm, a dielectric constant of 2.2, and a loss tangent of 0.0009. The structure is printed on a compact size of 0.32 λ0 × 0.30 λ0, where λ0 is the free-space wavelength at the centre frequency. A good agreement is obtained between the simulation and measurement performance. The designed filter-antenna with the achieved performance can find different applications for 2.4 GHz ISM band and 4G wireless communications.